Effect of cryopreservation on the acrosomal integrity of viable alpaca spermatozoa evaluated by flow cytometry - Pérez-Rosales, María (2020)
The aim of this study was to determine the effect of cryopreservation on acrosomal integrity in viable alpaca sperm. Samples from 46 alpaca testicles that had motility >30% and sperm concentration >50x106 sperm/ml were processed. Sperm recovered from the tail of the epididymis were separated into two 500 µl aliquots. The first aliquot was for the initial fresh evaluation and the second aliquot was frozen in straws and stored in liquid nitrogen until the evaluation of acrosomal integrity. For the evaluation of viability and acrosomal integrity, 100 µl of each sample were incubated with 2.5 µl of FITC-PSA (100 µg/ml) and 0.5 µl of propidium iodide (PI, 2.4 mM) for 10 min at 38 °C. Immediately afterwards, the samples were evaluated by flow cytometry, acquiring 10 000 events compatible with sperm per sample. FITC-PSA and PI were excited with a 488 nm laser, and fluorescence emission was detected using channels Ch02 (505-560 nm) for FITC-PSA and Ch05 (642-740 nm) for PI. The percentage of sperm with acrosomal integrity (FITC-PSA negative) of the population of viable sperm (PI negative) was determined. Wilcoxon's signed rank test was used to determine how cryopreservation affects acrosomal integrity in viable sperm. The acrosomal integrity of fresh viable spermatozoa (98.25 ± 5.41%) was found to be similar to that of viable post-thaw spermatozoa (98.75 ± 2.17%). It is concluded that viable alpaca sperm before and after the cryopreservation process maintain a high percentage of acrosomal integrity.